The Determinants Factors of Personal Mastery Among Clinical Nurse Practitioners in Indonesia - Kornelis Nama Beni; Nursalam Nursalam; M Hasinuddin; Diah Priyantini; Daviq Ayatulloh (Fundamental and Management Nursing Journal, 2024)
Introduction: Human resources of nursing who have low personal mastery have an impact on the quality and productivity of nursing services. Several factors have been studied to be associated with the low personal mastery of nurses. The purpose of this study was to analyze the factors that’s influencing personal mastery improvement of clinical nurse practitioners in a hospital.